Clinical Presentation and Outcomes among Children with Sepsis Presenting to a Public Tertiary Hospital in Tanzania - Kortz, Teresa Bleakly; Sawe, Hendry R.; Murray, Brittany; Enanoria, Wayne; Matthay, Michael Anthony; Reynolds, Teri (Frontiers in Pediatrics, 2017)
Background: Pediatric sepsis causes significant global morbidity and mortality and low- and middle-income countries (LMICs) bear the bulk of the burden. International sepsis guidelines may not be relevant in LMICs, especially in sub-Saharan Africa (SSA), due to resource constraints and population differences. There is a critical lack of pediatric sepsis data from SSA, without which accurate risk stratification tools and context-appropriate, evidence-based protocols cannot be developed. The study’s objectives were to characterize pediatric sepsis presentations, interventions, and outcomes in a public Emergency Medicine Department (EMD) in Tanzania. Methods: Prospective descriptive study of children (28 days-14 years) with sepsis (suspected infection with >2 clinical Systemic Inflammatory Response Syndrome [SIRS] criteria) presenting to a tertiary EMD in Dar es Salaam, Tanzania (July 1-September 30, 2016). Outcomes included: in-hospital mortality (primary), EMD mortality, and hospital length of stay. We report descriptive statistics using means and standard deviations, medians and interquartile ranges, and counts and percentages as appropriate. Predictive abilities of SIRS criteria, the Alert-Verbal-Painful-Unresponsive (AVPU) score and the Lambaréné Organ Dysfunction Score (LODS) for in-hospital, early and late mortality were tested. Results: Of the 2232 children screened, 433 (19.4%) met inclusion criteria, and 405 were enrolled. There were 247 (61%) subjects referred from an outside facility. Approximately half (54.1%) received antibiotics in the EMD, and some form of microbiologic culture was collected in 35.8% (n=145) of subjects. In-hospital and EMD mortality were 14.2% and 1.5%, respectively, median time to death was 3 days (IQR 1-6), and median length of stay was 6 days (IQR 1-12). SIRS criteria, the AVPU score, and the LODS had low positive (17-27.1%, 33.3-43.9%, 18.3-55.6%, respectively) and high negative predictive values (88.6-89.8%, 86.5-91.2%, 86.8-90.5%, respectively) for in-hospital mortality. Conclusions: This pediatric sepsis cohort had high and early in-hospital mortality. Current criteria and tested clinical scores were inadequate for risk-stratification and mortality prediction in this population and setting. Pediatric sepsis management must take into account the local patient population, etiologies of sepsis, healthcare system, and resource availability. Only through studies such as this that generate regional data in LMICs can accurate risk stratification tools and context-appropriate, evidence-based guidelines be developed.